2009
DOI: 10.1097/tp.0b013e3181aa7d87
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Delayed Graft Function and Wound Healing Complications After Deceased-Donor Kidney Transplantation Is not Affected by De Novo Everolimus

Abstract: Findings from this randomized, multicenter trial indicate that kidney function recovery, wound healing, efficacy, and tolerance are similar at 3 months posttransplant with immediate or DE in patients at protocol-specified risk of DGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 41 publications
4
55
2
Order By: Relevance
“…Kidney transplant patients receiving immunosuppressive therapy with mTOR inhibitors can benefit from less nephrotoxicity by reducing their exposure to CNIs 3, 4, 5, 6, 7, 8. There is a paucity of published data on the use of EVR in combination with Tac in de novo renal transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplant patients receiving immunosuppressive therapy with mTOR inhibitors can benefit from less nephrotoxicity by reducing their exposure to CNIs 3, 4, 5, 6, 7, 8. There is a paucity of published data on the use of EVR in combination with Tac in de novo renal transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion is a frequent occurrence after heart transplantation, with moderately to large effusions reported in approximately a fifth of recipients (73,(75)(76)(77). Mortality and hospital stay are unaffected (75)(76)(77), although one study suggested an association between pericardial effusions and acute rejection (78).…”
Section: Pericardial and Pleural Effusionsmentioning
confidence: 99%
“…46 This effect seems not to be associated with everolimus, and has not been seen in patients at risk of developing delayed graft function. 33,47 Wound healing problems and lymphocele formation have also been related to the use of proliferation signal inhibitors. These effects could be related to the antiproliferative effect of these drugs on fibroblasts.…”
Section: Long-term Safetymentioning
confidence: 99%